Serum Cytokinome Profile Evaluation: A Tool to Define New Diagnostic and Prognostic Markers of Cancer Using Multiplexed Bead-Based Immunoassays. (6th December 2016) - Capone, Francesca; Guerriero, Eliana; Sorice, Angela; Colonna, Giovanni; Ciliberto, Gennaro; Costantini, Susan
Abstract : In recent years, many researchers are focusing their attention on the link between inflammation and cancer. The inflammation is involved in the tumor development and suppression, by stimulating the immune response. In particular, the transition from chronic inflammation to cancer produces angiogenic and growth factors able to repair the tissue and to promote cancer cell survival, implantation, and growth. In this contest, the cytokines contribute to the development of these processes becoming active before and during the inflammatory process and playing an important function at the various disease levels. Thus, these proteins can represent specific markers of tumor development and progression. Therefore the "cytokinome" term is used to indicate the evaluation of cytokine pattern by using an "omics" approach. Newly, specific protein chips of considerable and improved sensitivity are being developed to determine simultaneously several and different cytokines. This can be achieved by a multiplex technology that, through the use of small amounts of serum or other fluids, is used to determine the presence and the levels of underrepresented cytokines. Since this method is an accurate, sensitive, and reproducible cytokine assay, it is already used in many different studies. Thus, this review focuses on the more latest aspects related to cytokinome profile evaluation in different cancers.